2012
DOI: 10.1186/1471-2172-13-56
|View full text |Cite
|
Sign up to set email alerts
|

Important role of CCR2 in a murine model of coronary vasculitis

Abstract: BackgroundChemokines and their receptors play a role in the innate immune response as well as in the disruption of the balance between pro-inflammatory Th17 cells and regulatory T cells (Treg), underlying the pathogenesis of coronary vasculitis in Kawasaki disease (KD).ResultsHere we show that genetic inactivation of chemokine receptor (CCR)-2 is protective against the induction of aortic and coronary vasculitis following injection of Candida albicans water-soluble cell wall extracts (CAWS). Mechanistically, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Therefore, neutrophils play an important role in CAWS-vasculitis and exhibit the characteristics of neutrophils such as (i) prolonged survival in inflammatory tissue, (ii) the production of a variety of inflammatory and tissue mediators in blood vessels, such as reactive oxygen species, arachidonate metabolites, proteases and glycosidases, are strongly related to the degradation and remodeling of blood vessels 36,37 . Furthermore, we found that CCR2, a receptor for MCP-1, deficient mice were resistant to CAWS-vasculitis 10 . As MCP-1 is a chemotactic factor for macrophages, the local accumulation of macrophages plays an equally important role to that of neutrophils.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, neutrophils play an important role in CAWS-vasculitis and exhibit the characteristics of neutrophils such as (i) prolonged survival in inflammatory tissue, (ii) the production of a variety of inflammatory and tissue mediators in blood vessels, such as reactive oxygen species, arachidonate metabolites, proteases and glycosidases, are strongly related to the degradation and remodeling of blood vessels 36,37 . Furthermore, we found that CCR2, a receptor for MCP-1, deficient mice were resistant to CAWS-vasculitis 10 . As MCP-1 is a chemotactic factor for macrophages, the local accumulation of macrophages plays an equally important role to that of neutrophils.…”
Section: Discussionmentioning
confidence: 79%
“…CAWS activated the lectin pathway of complement 8 , and was found to be a ligand for dectin-2 and the pattern recognition receptor (PRR) for pathogen-associated molecular patterns (PAMPs), having a C-type lectin structure 9 . Very recently, we and others have found that mice deficient in CCR2 and mice deficient in myeloperoxidase were resistant to CAWS-vasculitis 10,11 . In contrast to analyses for the molecular mechanisms of inflammation and immunity, the chemical structures required for CAWS-vasculitis have been limited.…”
Section: Introductionmentioning
confidence: 89%
“…In a murine model of vasculitis, Candida albicans watersoluble fraction (CAWS) is used as the inducer. Marked inflammatory change is observed in the aortic root, including the coronary arteries in CAWS-treated mice (89,90). While CCR2 and GM-CSF play an indispensable role in its pathogenesis (89,90), T and B cells are also involved in the vasculitis (89).…”
Section: Insight From Experimental Studies With Animal Model For Kdmentioning
confidence: 99%
“…To date, two other animal models of KD coronary arteritis have been established. These mouse models showed that crude microbe‐associated molecular patterns (MAMPs)/PAMPs from Lactobacillus caseii and Candida albicans induce acute coronary vasculitis (Table ). Thus, these animal studies confirmed that stimulation of innate immunity with molecules such as NOD1 ligands induces vasculitis that mimics the coronary artery lesions of KD.…”
Section: Kd Aetiologymentioning
confidence: 99%